Predicting cytomegalovirus infection and graft-versus-host disease using QuantiFERON-CMV and Monitor in pediatric transplants: a proof-of-concept study - Lina Souan; Rawad Rihani; Maher A. Sughayer (Therapeutic Advances in Hematology)
Background: Cytomegalovirus (CMV) infection can lead to significant morbidity and mortality in pediatric hematopoietic stem cell transplant recipients. Early detection of CMV infection is crucial for managing its impact. Aim: This study aims to evaluate the effectiveness of QuantiFERON-CMV ® (QF-CMV) and QuantiFERON-Monitor ® (QFM) tests in predicting CMV infection and graft-versus-host disease (GvHD) in pediatric hematopoietic stem cell transplant recipients to enhance patient outcomes and support personalized prevention strategies. Methods: The QF-CMV and QFM tests were used to predict CMV pp65 antigen and GvHD in 24 pediatric hematopoietic stem cell transplant recipients. Results: Data showed that positive CMV antigenemia (CMV-Ag) increased the risk of GvHD by 21.2%. QF-CMV and QFM were associated with CMV-Ag, with QF-CMV inversely predicting GvHD. Lymphocyte and neutrophil counts were positively linked to both tests. Conclusion: The findings suggest that QF-CMV and QFM tests could predict GvHD and CMV infection risk and help identify high-risk patients, contributing to personalized prevention strategies and improving CMV treatment. Despite the small sample size, this study is an essential proof of concept due to the unique patient population of pediatric bone marrow stem cell transplant recipients. Further multicenter studies are needed to validate these results.